Over-expression of brain-derived neurotrophic factor in mesenchymal stem cells transfected with recombinant lentivirus BDNF gene - Zhang, X.; Zhu, J.; Zhang, K.; Liu, T.; Zhang, Z. (Cellular and Molecular Biology, 2016)
This study was aimed at investigating the expression of brain-derived neurotrophic factor (BDNF) in mesenchymal stem cells (MSCs) modified with recombinant lentivirus bearing BDNF gene. Lentivirus vectors bearing BDNF gene were constructed. MSCs were isolated from rats and cultured. The lentiviral vectors containing BDNF gene were transfected into the MSCs, and BDNF gene and protein expressions were monitored with enhanced green fluorescent protein (EGFP). RT-PCR and Western blot were used to measure gene and protein expressions, respectibvely in MSCs, MSCs-EGFP and MSCs-EGFP-BDNF groups. Green fluorescence assay confirmed successful transfection of BDNF gene recombinant lentivirus into MSCs. RT-PCR and Western blot revealed that BDNF gene and protein expressions in the MSCs-EGFP-BDNF group were significantly higher than that in MSCs group and MSCs-EGFP group. There were no statistically signiï¬cant differences in gene expression between MSCs and MSCs-EGFP groups. MSCs can over-express BDNF when transfected with recombinant lentivirus bearing BDNF gene.